One new lignan derivative from the Combretum alfredii Hance. Issue 9 (3rd May 2017) - Bai, Meng; Wu, Li-Jun; Cai, Yue; Wu, Shou-Yuan; Song, Xiao-Ping; Chen, Guang-Ying; Zheng, Cai-Juan; Han, Chang-Ri
Abstract: One new lignan derivative 2, 3-dimethyl-4-(4-methoxyphenyl)-6, 7-dihydroxynaphthalene (1 ), together with five known compounds (2 –6 ), were isolated from ethanol extract of the branches and leaves of Combretum alfredii Hance collected in Hainan Province, China. Their structures were elucidated by the detailed analysis of comprehensive spectroscopic data. Compounds1, 2, 5 and6 were isolated from the genus of Combretum for the first time. All compounds were evaluated for their antibacterial activities. Compounds1 and2 showed significant antibacterial activities against six pathogenic bacteria. Abstract :